Growth hormone predicts bone density in elderly women. - Dennison, E; Hindmarsh, P; Kellingray, S; Fall, C; Cooper, C (2003)
Evidence is accumulating that the risk of osteoporosis may be influenced by environmental factors during intrauterine and early postnatal life; such programming might be mediated through modification of the GH/IGF-1 axis during critical periods in its development. To address this issue, we explored the relationships among birth weight, circulating GH profile, bone density, and bone loss rate in a group of British women. The study population consisted of 38 women 60-75 years old resident in Hertfordshire for whom detailed birth records were available. Twenty-four-hour circulating GH profiles were obtained during an inpatient stay on a metabolic ward, after an overnight rest. The circulating profile of GH was characterised by estimating the peak, median, trough, and total concentrations from 72 samples measured sequentially over 24 h in each subject. Bone mineral density was assessed at the lumbar spine and femoral neck at baseline and at follow-up 4 years later. Lumbar spine bone mineral content (BMC) and density (BMD) were positively associated with all measures of GH concentration, although relationships were strongest for BMC with trough GH (r = 0.47, P < 0.01). Associations persisted after adjustment for age, body mass index, smoking, alcohol consumption, physical activity, and osteoarthritis score in multiple regression models. However, associations of GH concentration with femoral neck BMC were weak, and there was no association between any measure of GH concentration and bone loss at either site. Total (integrated) daily GH concentration tended to increase (P = 0.08) with rising birth weight, while IGF-1 concentration fell (P = 0.05) with rising birth weight, suggesting a role for the GH/IGF-1 axis in the programming of adult bone mass among women.